Inverse double-C shaped square split ring resonator based metamaterial with multi-resonant frequencies for satellite band applications - Siddikya, M.; Mohammad, R. I. F.; Mohammad, T. I.; Sabirin, A,; Khandaker, Mayeen Uddin * (Elsevier, 2020)
In this research article, horizontally placed inverse double-C shaped horizontally placed square split ring resonator (SSRR) based metamaterial with multi-resonant frequencies is presented for satellite band applications. The metamaterial has an artificially established structure on a dielectric substrate smaller than the wavelength of electromagnetic (EM) wave, which helps introduce new significant characteristics that can be achieved through a geometrical shape arrangement using external stimuli. The proposed metamaterial structure using a highfrequency structural simulator based on a finite integration technique to configure the electromagnetic properties. Five resonant frequencies with the different bandwidths for this unit cell are located between 2.47 and 2.75, 5.70–5.85, 7.04–8.09, 9.70–10.08 and 12.40–12.60 GHz respectively. This unit-cell structure are shown to better performance on effective parameters and size mitigation that make preferable to industrial collaboration for radar and satellite frequency applications with wider bandwidth and higher gain. The proposed SSRR structures were deployed to analyse the parametric studies using different substrate types, array designs and structural optimization.